A Case Report : Modality Treatment With Mineralcorticoid And Radikal Reseksi To Total Reseksi In Pediatric Brain Tumor - Karentina, Yugita Utami Nora; Aswuri, Sandra Pradita Widya; Sulistyaningsih, Indhah Meilani; Kusumastuti, Dian Ayu Suci Dwi; Nugraha, Eki Adetya (Jurnal EduHealth, 2024)
Brain tumor are the second most common neoplasm and the most common solid tumor in children. Fifty percent to 60% of childhood brain tumors originate in the posterior fossa. These include medulloblastomas, cerebellar astrocytomas, and fourth ventricle ependymomas. The remaining 40% to 50% of childhood brain tumors are supratentorial and include astrocytoma, hypothalamic and optic pathway tumors, and craniopharyngiomas. A 19 year old child came to the hospital emergency room with complaints of dizziness. Dizziness is accompanied by headaches that dissapearing. Complaints have been felt since about half a year but have worsened for one week before at emergency room. While being treated at the hospital, the patient experienced a seizure once, when the seizure was felt for 2 minutes, it was a whole body type of seizure. Patients also experience nausea and decreased appetite. Consciousness is still fully conscious. In this case, patien can be treatment IVFD Ringer Lactate 135 cc/hour, Metamizole 250 mg/1 ml /8 hour IV, Diphenhidramin 5 mg /12 hour IV, Dexamethasone 5 mg /8 hour IV, Piracetam 500 mg/12 hour IV. In this case, Dexamethasone therapy is given which is the corticosteroid of choice in these patients because of its low mineralocorticoid activity and only reduces the symptoms caused optimally. The goal is to reduce neurological symptoms but with a dose that is lowered slowly. The main treatment is still tumor resection with neurosurgeon.